A giant African millipede re-discovered, re-located and re-classified after 120 years (Diplopoda, Spirobolida, Pachybolidae) - Fiemapong, Armand Richard Nzoko; Enghoff, Henrik (Zootaxa, 2018)
The giant millipede Pachybolus tectus Cook, 1897, described from Zanzibar, East Africa, and never re-collected till now, is re-described based on newly collected specimens from Cameroon, West Africa. The species is transferred to the genus Pelmatojulus Saussure, 1860, and compared with the most similar congener, P. togoensis (Cook, 1897). The type specimen of P. tectus, which no longer exists, probably was mis-labelled. An overview of the distribution of Pelmatojulus species and records of the genus from Cameroon are given, including P. brachysternus (Cook, 1897) as new to the fauna of Cameroon. Pelmatojulus insignis (Saussure, 1859) and P. togoensis are recorded as new to the fauna of Ghana.